2018
DOI: 10.1242/dev.160127
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-guided Notch-dependent gliogenesis byDrosophilamulti-potent progenitors

Abstract: Macroglial cells in the central nervous system exhibit regional specialization and carry out region-specific functions. Diverse glial cells arise from specific progenitors in specific spatiotemporal patterns. This raises an interesting possibility that glial precursors with distinct developmental fates exist that govern region-specific gliogenesis. Here, we have mapped the glial progeny produced by the type II neuroblasts, which, like vertebrate radial glia cells, yield both neurons and glia via intermediate n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 82 publications
2
31
0
Order By: Relevance
“…This allows targeted lineages to be parsed according to the properties of the mature neurons to which they give rise using cell-type specific Gal4 drivers. Such so-called “cell class-lineage intersections” have been previously performed to identify subsets of neurons generated by Type II NBs of the Drosophila brain, which can be selectively targeted using a Type II-specific enhancer (Ren et al, 2016; Ren et al, 2018; Ren et al, 2017). Among the neurons generated by Type II NBs are several populations of dopaminergic neurons, identified by a Tyrosine Hydroxylase-specific Gal4 driver (TH-Gal4).…”
Section: Resultsmentioning
confidence: 99%
“…This allows targeted lineages to be parsed according to the properties of the mature neurons to which they give rise using cell-type specific Gal4 drivers. Such so-called “cell class-lineage intersections” have been previously performed to identify subsets of neurons generated by Type II NBs of the Drosophila brain, which can be selectively targeted using a Type II-specific enhancer (Ren et al, 2016; Ren et al, 2018; Ren et al, 2017). Among the neurons generated by Type II NBs are several populations of dopaminergic neurons, identified by a Tyrosine Hydroxylase-specific Gal4 driver (TH-Gal4).…”
Section: Resultsmentioning
confidence: 99%
“…Transgenes used for twin-spot MARCM for vnd lineages include: vnd-T2A-GAL4 (this study), UAS-KD, dpn>KDRT-stop-KDRT>Cre:PEST, nSyb>loxP-stop-loxP>LexA∷p65, hs-FLP, FRT40A, lexAop-mCD8∷GFP-insulated spacer-lexAop-rCD2i, and lexAop-rCD2∷RFP-insulated spacer-lexAop-GFPi [16]. Transgenes used for Notch depletion include: hs-ATG>KOT>FLP [27], ase-KD (this study), dpn>FRT-stop-FRT>Cre::PEST [16], actin^loxP-stop-loxP^Gal4 (this study), UAS-Notch-RNAi (BL#33611), USA-mCD8::GFP [10].…”
Section: Fly Strains and Dna Constructsmentioning
confidence: 99%
“…bodies are neural structures that are highly dependent on glia-neuron interactions. It has 565 been shown that glia wrap the peduncle and the lobes during development (Spindler et 566 al., 2009) and in the adult (Kremer et al, 2017), and that different type II DM 567 neuroblasts contribute glia that associate with the mushroom body (Ren et al, 2018). In 568 control animals, ClC-a + glia surrounded the MB calyx ( Figure 8B) and the peduncle 569 ( Figure 8D).…”
mentioning
confidence: 94%
“…Ren et al, 2018;Viktorin et al, 2013). We repeated DL1 lineage-tracing experiments 435 and observed that progeny from the DL1 populated the OL following the same temporal 436 pattern as ClC-a + boundary glia (SupplementaryFigure 8D-F).…”
mentioning
confidence: 99%